2014
DOI: 10.1186/1129-2377-15-22
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the vasodilator responses of isolated human and rat middle meningeal arteries to migraine related compounds

Abstract: BackgroundMigraine attacks occur spontaneously in those who suffer from the condition, but migraine-like attacks can also be induced artificially by a number of substances. Previously published evidence makes the meninges a likely source of migraine related pain. This article investigates the effect of several vasodilators on meningeal arteries in order to find a connection between the effect of a substance on a meningeal vessel and its ability to artificially induce migraine.MethodsA myograph setup was used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 46 publications
(49 reference statements)
2
19
0
Order By: Relevance
“…Interestingly, the IS caused a strong contraction of the artery, whereas nothing occurred with the artery tone following the CFA administration. Vasodilatation has been suggested to be the initiator of migraine, but could also be a consequence or a side phenomenon [ 44 ] and it has previoulsy been shown that not all migraine attacks are associated with vasodilation [ 45 ]. An earlier study supporting the vascular hypothesis found that a short period of vasoconstriction triggers the release of vasodilator agents, such as CGRP, and could explain some of the findings presented here [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the IS caused a strong contraction of the artery, whereas nothing occurred with the artery tone following the CFA administration. Vasodilatation has been suggested to be the initiator of migraine, but could also be a consequence or a side phenomenon [ 44 ] and it has previoulsy been shown that not all migraine attacks are associated with vasodilation [ 45 ]. An earlier study supporting the vascular hypothesis found that a short period of vasoconstriction triggers the release of vasodilator agents, such as CGRP, and could explain some of the findings presented here [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Migraine presents two subtypes, migraine with aura and migraine without aura ( Silberstein et al, 2005 ). Although a large number of recent studies have tried to establish the migraine pathophysiology ( Bhaskar et al, 2013 ; Noseda and Burstein, 2013 ; Sarrouilhe et al, 2014 ; Thissen et al, 2014 ), the role of the neural and vascular mechanisms in this process has been largely discussed in the literature, ( Asghar et al, 2011 ; Grände et al, 2014 ). As a matter of fact, there is still a debate whether the source of the pain is in the nerves around the cranial arteries, CNS or both ( Goadsby et al, 2009 ; Olesen et al, 2009 ).…”
Section: Is Migraine Pathophysiology Correlated To a Bbb Dysfunction?mentioning
confidence: 99%
“…Collectively, those results suggest a key role of cranial blood vessels in the migraine pathophysiology. In fact, meningeal arteries lack BBB and represent much more permeable structures, compared with cortical vessels ( Edvinsson and Tfelt-Hansen, 2008 ; Grände et al, 2014 ). There have been considerable advances in the understanding of the sequence of events that lead to a migraine headache.…”
Section: Is Migraine Pathophysiology Correlated To a Bbb Dysfunction?mentioning
confidence: 99%
“…On the other hand, there are no studies reporting visualizing the MMA or assessing its blood flow. Ultrasonographic visualization of the MXA and its MMA branch in ITF may allow their assessment in headache and migraine, intracranial hematomas, and extracranial‐intracranial by‐pass surgery, as well as to assess collateral flow development in carotid occlusive diseases and the vascularization of tumors and vascular malformations of the facial region …”
Section: Introductionmentioning
confidence: 99%
“…Ultrasonographic visualization of the MXA and its MMA branch in ITF may allow their assessment in headache and migraine, intracranial hematomas, and extracranial-intracranial by-pass surgery, as well as to assess collateral flow development in carotid occlusive diseases and the vascularization of tumors and vascular malformations of the facial region. 2,[6][7][8][9][10] The aim of this study was to develop and present a method to visualize the MMA and MXA in the ITF, correctly identify these two arteries based on their anatomy and blood-flow features, and describe their hemodynamic characteristics in a group of subjects without vascular disease. After the visualization of the arteries, we measured the depth of insonation (DI), and obtained the pulsed Doppler signal of the MXA and the MMA, on which we measured the angle corrected peak We anticipated that the Doppler spectrum characteristics of MXA and MMA would be intermediate between those of extra and intracranial arteries 12,13 (Figure 3).…”
Section: Introductionmentioning
confidence: 99%